Studi Kebijakan Pengembangan Kurikulum Pendidikan Agama Islam Model Kurikulum 2013 - Ahmad Wahyu Hidayat (AL-MURABBI: Jurnal Studi Kependidikan dan Keislaman, 2020)
Abstract: Curriculum development is a process of activities that produce conceptual, material, frame of mind, and curriculum which are developed through the preparation, implementation, assessment and refinement after completion, so there is a verification stage so that it can be seen as feasible and not a new curriculum candidate as a result of development carried out in the curriculum. This study discusses in depth about the development of curriculum PAI 2013 Curriculum model. This study aims to determine the extent of the study of the development of Islamic education curriculum curriculum curriculum models in 2013. This research uses the literature review method. Data collection was carried out using documentation study techniques. The results of this study are seen in the components of the PAI curriculum which each have correlations and are interrelated as a form of cooperation in the realization of the PAI curriculum so that it remains relevant to the reality, time, community conditions, student conditions, and the development conditions of science and technology. It should be emphasized in the PAI curriculum that is the process of instilling Islamic values ​​as the main axis that is characteristic. Nevertheless educators continue to strive in developing curriculum especially on PAI material so that the PAI learning system remains interesting to answer the challenges of the times and make PAI material as attractive as possible so that students who have critical reasoning and are unusually intelligent are not saturated and autistic. We can see the common thread that one component of the PAI learning system is the PAI curriculum which consists of several components, namely objectives, materials, methods, and evaluation. While the other components of the PAI learning system are educators, students, institution managers, and learning resources besides educators. So the authors propose by adding religious and collaborative values ​​to maximize the PAI curriculum in implementing it in schools.